A justiça como equidade segundo John Rawls - Fernandes, José Carlos Lopes (2010)
This essay aims to examine the theoretical foundations of John Rawls in his book "A theory of Justice". Research is rooted in "part 1 Theory", on which we are discussing to extract the ideas of the concept of "justice as fairness", because this issue is a detailed theory in drawing up a new conception of Justice with the idealization of a fairer society. The correction of social injustice, can only come from the practice of a policy directed to fairness. According to John Rawls, justice becomes a political obligation to fair cooperation system, which is the society. Observing that the theory of Rawls develops according to an idea of an well orderly society. And this would be the one regulated by a conception of Justice, i.e. a fair system of cooperation, which is based on a public conception of justice. This way, citizens are equal with regard of having a minimum degree of moral faculties necessary to participate in social cooperation during all their life of plans. Thus, we demonstrated that the theory of "justice as fairness", proposed by Rawls, shows itself an innovative proposal to modern society, because it seeks for social integration and policy through a justification of norms and principles of justice.